Correlation of Force to Deformation of the Anterior Bundle of the Medial Collateral Ligament Through Consideration of Band Laxity. Issue 9 (18th June 2019) - Jordan, David; Schimoler, Patrick; Kharlamov, Alexander; DeMeo, Patrick J.; Miller, Mark Carl
ABSTRACT: The anterior bundle of the medial collateral ligament (AMCL) resists the loads that arise at the elbow during overhand throwing and has commonly been divided into posterior and anterior bands. While these anterior and posterior bands have been thought to bear the load at different flexion angles, any transition of the load distribution between the two bands is poorly understood and has not considered laxity (slack). This study considers the AMCL as three bands and quantifies the mechanical response to vertical distraction, simulating valgus‐load joint opening, through the sequential superposition of the band responses after the elimination of inherent laxity. Eight cadaveric elbow specimens were used for the study. The intact AMCL of each specimen was tested under vertical distraction in a specialized load frame at four elbow flexion angles and then subsequently retested after two longitudinal transections. The greatest laxity at full extension and full flexion belonged to the posterior (1.9 mm) and anterior (2.4 mm) band, respectively. At the lesser and higher flexion angles, the greatest structural stiffness belonged to the anterior and middle band. The overall AMCL was the most structurally stiff at 60°, with approximately 150 N of force required for 2% elongation. This study shows that the different bands of the AMCL may have different load bearing properties at different flexion angles, causing each band to support different proportions of an imposed load. The presence of the laxity may impose a load‐bearing delay, causing load‐bearing in each band to begin asynchronously. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:2027–2034, 2019